(3bGYOI ajeG jLH Ydi Gdecda Cf jYJbOgs ((3CHh SYjO eNdha Hf eMeO Hf Ydi GdJjedi s)
(3ChdgG (B:s
(3EYde CQTOfG Gddg hEjGc Cfg hLH Ydi cd ecda Cf jYde Cf Gddg YR hLd hGMO ai edcg Ndb GdYGde HCSQg GdYdhi hGdSadi hGdYQT hGdcQSi , hGdSehGJ hGdCQV heG ajgeG hHjfgeG s
(3BNQgG (B:s
(3djS ceKdg TF hgh GdSejY GdHUjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJUha hGdBOGH GdTQYjIs